2015
DOI: 10.1002/bit.25496
|View full text |Cite
|
Sign up to set email alerts
|

Temperature‐dependent control of Staphylococcus aureus biofilms and virulence by thermoresponsive oligo(N‐vinylcaprolactam)

Abstract: Bacterial biofilms are associated with persistent infections because they are highly tolerant of antimicrobial agents, and in the case of Staphylococcus aureus, which is a leading cause of nosocomial infections because of its resistance to diverse antibiotics, biofilm formation is a known mechanism of drug resistance. In the present study, we investigated the ability of thermoresponsive oligo (N-vinylcaprolactam) (OVCL) to control biofilm formation by and the virulence of S. aureus. One synthetic and four comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…In particular, α-toxin (Hla) causes hemolysis 29 and contributes to biofilm formation 8 . In the present study, alizarin, purpurin, and quinalizarin showed antibiofilm and anti-hemolytic activities ( Figs 3 and 5 ), and previous studies have shown that several flavonoids 16 , nerolidol 22 , stilbenoids 40 , and thermoresponsive oligo ( N -vinylcaprolactam) 41 have antibiofilm activity and anti-hemolytic activity against S. aureus . Thus, it appears there is a positive relation between antibiofilm and anti-hemolytic activities.…”
Section: Discussionsupporting
confidence: 82%
“…In particular, α-toxin (Hla) causes hemolysis 29 and contributes to biofilm formation 8 . In the present study, alizarin, purpurin, and quinalizarin showed antibiofilm and anti-hemolytic activities ( Figs 3 and 5 ), and previous studies have shown that several flavonoids 16 , nerolidol 22 , stilbenoids 40 , and thermoresponsive oligo ( N -vinylcaprolactam) 41 have antibiofilm activity and anti-hemolytic activity against S. aureus . Thus, it appears there is a positive relation between antibiofilm and anti-hemolytic activities.…”
Section: Discussionsupporting
confidence: 82%
“…) and to the controlling of cell‐surface hydrophilicity and haemolytic activity (Lee et al . ), respectively. Here, we report for the first time that OVCL MW 679 inhibits biofilm and hyphal formation and cell aggregation by C. albicans (Figs , and ).…”
Section: Resultsmentioning
confidence: 95%
“…) and Staphylococcus aureus (Lee et al . ), respectively. In the present study, OVCL/PLGA coatings on glass were found to have antibiofouling effects on C. albicans (Fig.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The basic principle involves causing irreversible damage in pathogenic cells by activating metal NPs or polymer-based systems using external energy sources, such as visible light [214], temperature [215], near-infrared (NIR) radiation [216], or high frequency alternating magnetic fields (AMF) [217]. Gold, iron oxide, and graphene NPs have been utilized as photothermal agents that absorb NIR light and convert this into heat energy.…”
Section: Nanotechnology Based Strategies For Biofilm Control and Tmentioning
confidence: 99%